A Systematic Literature Review of Korea’s Testing Culture: Surveying the Landscape from An Ecological Perspective - Kim, Taeri; Lim, Dongwon; Pyun, Minji; Rhee, Jung Ik (Technium Education and Humanities, 2025)
This systematic review evaluates the research on pervasive testing culture in South Korea from an ecological perspective. The prioritization of testing in South Korean education is a defining feature of the educational system. Our study synthesizes findings from 46 studies, evaluating them through an ecological lens to understand trends in how much attention is paid to learning while analyzing which levels of the ecological system are over- and under-represented. We find that while much research highlights the impacts of testing culture on students’ identity, limited research links testing culture to learning itself. Of those studies that do, most center on individual and interpersonal levels, neglecting broader cultural and societal contexts. Additionally, limited evidence exists on pervasive testing and conceptual understanding.